Peningkatan Daya Saing Telur Gabus Almetta Jambi Melalui Inovasi Kemasan, Digital Marketing, dan Keuangan: Pengabdian - Liona Efrina. S; Evrina Evrina; Ikke Yamalia; Eka Maryatni; Fery Purnama; Azwani Aulia; Bella Hartati (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
Almetta Egg Strips Micro, Small and Medium Enterprises (UMK) is a home industry established in 2011 in Jambi City, owned by Mrs. Dewi Safrida, with 11 employees in production, packaging, and marketing. The products produced include egg strips, various chips, and rempeyek, which have been marketed in local stores, but have not yet entered modern retail due to limited packaging and financial records. An initial survey identified three main problems: conventional marketing, low literacy and technology-based financial records, and limited production equipment. This PKM activity aims to increase the competitiveness of MSEs by strengthening digital marketing, financial management, and modernizing production equipment. The program was implemented for eight months in a participatory manner by lecturers and students of Adiwangsa University Jambi through digital marketing and e-commerce training, digital financial application assistance, online store development, and the provision of production equipment. Activity outputs included redesigning packaging according to modern retail standards, implementing the SIApik application, preparing simple financial reports, and activating social media and online stores. As a result, partners have implemented digital financial recording, online marketing has begun to develop, and production efficiency and quality have increased, so that MSEs have become more modern, efficient, and adaptive to the digital economy and support the achievement of SDGs, KPIs, and the vision of Adiwangsa University Jambi.